The pardoner's tale, and other plays - Yates, Irene; Copley, Paul Barrett, Stan Lanyon, Angela (Heinemann Educational Oxford, 1999)
Literacy World is evolving with the renewed Framework to provide all the support you need to deliver Shared Reading and Writing, Guided Reading, ICT and Speaking and Listening at Key Stage 2/P4-7. A wealth of quality resources, exceptional teacher support and complete differentiation makes Literacy World your only choice for fiction and non-fiction at Key Stage 2/P4-7.